School Resource Officers' Roles Differ in the Prediction of Nonviolent and Serious Violent Incidents. Issue 2 (3rd July 2021) - Stevens, Tara; Barnard-Brak, Lucy; Jackson, Jesseca
Abstract: School resource officers' (SROs) presence (e.g., engagement in patrol, carrying firearms, etc.) and prevention (e.g., mentoring, teaching) roles have not been distinguished in investigations of SROs' association with student outcomes. A model predicting nonviolent incidents and serious violent incidents reported to police from SRO presence and prevention roles while controlling for limits in mental health availability, teacher training, and school problems was fit to an archival dataset of 1529 school administrators' responses to the School Survey on Crime and Safety (SSCOS). SRO prevention significantly predicted lower numbers of nonviolent incidents reported to police (β = −.28) and SRO presence significantly predicted higher numbers of nonviolent (β = .51) and serious violent (β = .24) incidents reported to police in the high school sample. SRO presence and SRO prevention were not significantly associated with either nonviolent or serious violent incidents reported to police in the middle level sample. Greater acknowledgement of limitations in mental health service availability was associated with reports of school problems across samples, and school problems were significantly associated with higher numbers of nonviolent and serious violent incidents reported to police. Results suggest that investment in the SRO prevention role over presence is needed. Impact Statement In high schools employing school resource officers (SROs), law enforcement SRO presence was associated with higher levels of nonviolent and serious violent incidents reported to police, whereas the SRO prevention role was associated with lower levels of nonviolent and serious violent incidents reported to police. Only mental health availability had a significant influence on reducing school problem behavior across middle and high schools. Investment in the SRO prevention role over presence is needed, and collaboration with other mental health professionals to support the SRO preventative role is suggested.